Integrated Aquaculture-Agriculture (IAA) Systems in Minya - Sbaay, Ashraf; Shaheen, Hussam; Mosbah, Menna; Nasr-Allah, Ahmed (WorldFish, 2024)
Under the flagship of F2R-CWANA, on September 23rd, 2024, WorldFish conducted a one-day workshop in Minya governorate. The workshop took place at the Armed forces hotel in collaboration with two CGIAR centers; The International Center for Agricultural Research in the Dry Areas (ICARDA), and The International Water Management Institute (IWMI). A total of 51 participants attended the workshop sessions, which included a mix of input presentations and interactive discussions focused on case studies and lessons learned. The participants represented a diverse range, including small-scale to medium-scale farmers, producers, and hatchery and farm owners.